Assessing affirmative action practices in Nepal’s federal civil service: Current achievements and future reform needs - Bhul, Baburam (Nepal Public Policy Review, 2025)
Nepal has implemented an affirmative action policy in the federal civil service since 2007 to address historical injustices and inequalities and promote the representation of marginalized people, such as women, ethnic minorities, and underprivileged castes, in public sector employment. This move has contributed to empowering disadvantaged people, mainstreaming minorities, and promoting social justice by strengthening inclusion within the bureaucratic structure. A qualitative research methodology is applied to perform a scoping review of 87 scholarly articles and a media review of 45 news articles to reveal the reasons behind the reforms made by policy enterprises in Nepal. The findings scrutinize both the constructive and critical facets of affirmative action practices in Nepal’s public service from 2007 to 2024. Besides some positive results leading to cultural competencies, such as the increased representation of women, Dalits, and ethnic minorities, there are still substantial inequalities in equal opportunities for empowerment and active participation in decision-making processes. The main reasons for such negative situations are complex social, ideological, and legal barriers, narrow-minded and deeply established prejudices, the lack of sufficient financial and human resources to undertake the programs, patriarchal organizational culture, and ultimately inadequate political commitment. The paper recommends continued reforms, timely review, preventing elite capture, adaptation to changing needs, a focus on the inadequate representation of marginalized groups, and the promotion of affirmative action policies that will result in the ending of these hurdles and, eventually, a more representative and all-inclusive Nepalese civil service.